2009
DOI: 10.1017/s030500090800929x
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in acoustic modifications of Mandarin maternal speech to preverbal infants and five-year-old children: a longitudinal study

Abstract: Acoustic-phonetic exaggeration of infant-directed speech (IDS) is well documented, but few studies address whether these features are modified with a child's age. Mandarin-speaking mothers were recorded while addressing an adult and their child at two ages (7-12 months and 5 years) to examine the acoustic-phonetic differences between IDS and child-directed speech (CDS). CDS exhibits an exaggeration pattern resembling that of IDS-expanded vowel space, longer vowels, higher pitch, and greater lexical tone differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
97
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(112 citation statements)
references
References 25 publications
9
97
0
6
Order By: Relevance
“…Infant-directed speech has also been hypothetized to facilitate language learning [6] by supporting the construction of phonetic and vowel categories [7,8], the clearer production of consonants [3] and the acquisition of new words [9]. This role in language learning is consistent with the decrease in the use and acoustic specificity of infant-directed speech that follows the development of language skills during the first year of the child [10][11][12]. At a proximal level, these dynamic changes could be explained by modifications of the baby's reactions to speech.…”
Section: Introductionmentioning
confidence: 88%
“…Infant-directed speech has also been hypothetized to facilitate language learning [6] by supporting the construction of phonetic and vowel categories [7,8], the clearer production of consonants [3] and the acquisition of new words [9]. This role in language learning is consistent with the decrease in the use and acoustic specificity of infant-directed speech that follows the development of language skills during the first year of the child [10][11][12]. At a proximal level, these dynamic changes could be explained by modifications of the baby's reactions to speech.…”
Section: Introductionmentioning
confidence: 88%
“…Most of the studies that investigated vowel hyperarticulation in speech to normal-hearing infants relative to adult-directed (AD) speech have focused on vowel contrasts that are differentiated by one primary acoustic dimension (e.g., formant frequencies) in the phonological system of the native language (Burnham et al, 2002;Kuhl et al, 1997;Lam and Kitamura, 2010;Liu et al, 2009;Uther et al, 2007). A recent study by Englund and Behn (2005) also demonstrated that Norwegian mothers exaggerate spectral properties and vowel duration that are both phonologically distinctive features in Norwegian.…”
Section: Introductionmentioning
confidence: 99%
“…Infant directed speech (IDS) and childdirected speech (CDS) consist of utterances that are shorter, more repetitious, and higher and more varied in pitch in comparison to adultdirected speech (ADS; Fernald & Simon, 1984;Snow, 1977). IDS and CDS are also characterized by vowels that are longer in duration and more "stretched" in acoustic space (Englund & Behne, 2005;Kuhl et al, 1997;Liu, Tsao, & Kuhl, 2009).…”
Section: Discussionmentioning
confidence: 99%